The ostrich mycoplasma Ms01 : the identification, isolation, and modification of the P100 vaccine candidate gene and immunity elicited by poultry mycoplasma vaccines - Pretorius, Benita (Stellenbosch : Stellenbosch University, 2017)
Thesis (MSc)--Stellenbosch University, 2009.